HhaI and HpaII DNA methyltransferases bind DNA mismatches, methylate uracil and block DNA repair. - Yang, A S (1995)
The hydrolytic deamination of 5-methylcytosine (5-mC) to thymine (T) is believed to be responsible for the high mutability of the CpG dinucleotide in DNA. We have shown a possible alternate mechanism for mutagenesis at CpG in which HpaII DNA-(cytosine-5) methyltransferase (M.HpaII) can enzymatically deaminate cytosine (C) to uracil (U) in DNA [Shen, J.-C., Rideout, W.M., III and Jones, P.A., Cell, 71, 1073-1080, (1992)]. Both the hydrolytic deamination of 5-mC and enzymatic deamination of C create premutagenic DNA mismatches (G:U and G:T) with the guanine (G) originally paired to the normal C. Surprisingly, we found that DNA-(cytosine-5) methyltransferases have higher affinities for these DNA mismatches than for their normal G:C targets and are capable of transferring a methyl group to the 5-position of U, creating T at low efficiencies. This binding by methyltransferase to mismatches at the recognition site prevented repair of G:U mismatches by uracil DNA glycosylase in vitro.